(untitled) - Zinn, Maxine Baca (New York, 1996)
The book treats diversity as the norm on modern family life, exploring the many varieties of familial relationships found in American society today. Viewing the family on both "macro" and "micro" levels, it examines the influence of large social trends on personal experience with particular attention to gender, race, class, and economic factors.
Keywords: Family,Social conditions; United States,United States